The Elite : The Story of Special Forces - From Ancient Sparta to the War on Terror - Fiennes, Ranulph (London Simon & Schuster, 2019)
The best of the best, these elite units have frequently been immortalised on the big screen and in computer games for their daring deeds. Whether it be fighting on the battlefield, storming forts and castles, rescuing hostages, high stakes reconnaissance missions or the dramatic assassination of enemy leaders, these are the men who are relied upon to undertake dangerous missions of the highest stakes. While celebrating the heroics of groups such as the SAS and Navy Seals, Sir Ranulph also reveals the true stories of infamous organisations such as The Assassins and Templar Knights. Uncovering their origins, and examining their weapons and tactics, Sir Ranulph showcases these units most famous missions, and reveals the men behind them. Showing incredible courage, often in the face of impossible odds, these units have also changed the course of history along the way. Sir Ranulph discusses the reasons behind their success and failures, with many notorious conflicts often being decided by these elite units facing off against each other, with the victor not only evolving warfare, but also consigning their opponent to history. While these units traditionally prefer to operate in the shadows, Sir Ranulph brings their remarkable histories to the fore, told with his trademark ability to weave a story which has seen him become one of Britain's most beloved bestselling authors.
Include Color illustrations and Index
Keywords: Special forces (Military science)